1995
DOI: 10.1007/bf02065522
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of extracorporeal piezoelectric lithotripsy (EPL) and intracorporeal electrohydraulic lithotripsy (EHL) in difficult bile duct stones

Abstract: Today, nearly 90% of common bile duct stones are extracted endoscopically. Problems are encountered if there are large stones or a duct stenosis. Extracorporeal piezoelectric lithotripsy (EPL) as well as intracorporeal electrohydraulic lithotripsy (EHL) serve as an alternative to surgical intervention for those few patients in whom endoscopic measures have failed. A total of 35 patients with common bile duct stones in whom conventional endoscopic treatment had failed were selected on the condition that stone v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 26 publications
2
14
1
4
Order By: Relevance
“…The reported problems of ESWL are further incarceration and/or injuries to the distal pathway caused by fragmented stones [10,11]. However, anatomical characteristics in patients after choledochal cyst excision and hepatico-enterostomy could compensate the problems.…”
Section: Discussionmentioning
confidence: 98%
“…The reported problems of ESWL are further incarceration and/or injuries to the distal pathway caused by fragmented stones [10,11]. However, anatomical characteristics in patients after choledochal cyst excision and hepatico-enterostomy could compensate the problems.…”
Section: Discussionmentioning
confidence: 98%
“…Electrohydraulic lithotripsy has been shown to be an effective tool for the endoscopist [1] and surgeon [13,18]. Lezoche et al [13] have reported that intraoperative choledochoscopy and EHL may be combined for treatment of unsuspected CBD stones discovered at laparoscopic cholecystectomy with routine cholangiography.…”
Section: Discussionmentioning
confidence: 99%
“…Adamek and colleagues compared extracorporeal piezoelectric lithotripsy (EPL) to intracorporeal EHL in patients with failed duct clearance using standard approaches, in which 13 patients had large stones [28]. Assessing 35 patients that met the inclusion criteria, they found that EHL was associated with less lithotripsy sessions than EPL (1.4 versus 2.3); both techniques required additional endoscopy, with almost half the patients requiring three.…”
Section: Methods To Decrease the Size Of Stonesmentioning
confidence: 99%